2014
DOI: 10.1186/1471-2474-15-68
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of low back pain: a meta-analysis comparing outcomes in randomised clinical trials (RCTs) and observational studies

Abstract: BackgroundEvidence suggests that the course of low back pain (LBP) symptoms in randomised clinical trials (RCTs) follows a pattern of large improvement regardless of the type of treatment. A similar pattern was independently observed in observational studies. However, there is an assumption that the clinical course of symptoms is particularly influenced in RCTs by mere participation in the trials. To test this assumption, the aim of our study was to compare the course of LBP in RCTs and observational studies.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 112 publications
6
45
2
Order By: Relevance
“…These reviews included only randomized controlled trials (RCT) and caution must be shown when comparing with observational studies like ours where therapists may use different treatments and also individually adapt the treatment to each patient. However, studies of subjects with low back pain suggest that the course of pain may be unrelated to study designs (Artus et al, 2014). The absolute change in pain at two months in our study was modest and only marginally larger than the natural course of neck pain observed in a general population study, which reported an absolute change of 1 point on NRS at two months after the start of a neck pain episode .…”
Section: Discussioncontrasting
confidence: 77%
“…These reviews included only randomized controlled trials (RCT) and caution must be shown when comparing with observational studies like ours where therapists may use different treatments and also individually adapt the treatment to each patient. However, studies of subjects with low back pain suggest that the course of pain may be unrelated to study designs (Artus et al, 2014). The absolute change in pain at two months in our study was modest and only marginally larger than the natural course of neck pain observed in a general population study, which reported an absolute change of 1 point on NRS at two months after the start of a neck pain episode .…”
Section: Discussioncontrasting
confidence: 77%
“…, 2014). Thus, a considerable number of patients are treatment non‐responders or discontinue the therapy because of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Some would argue that when assessing prognosis, a 12-month follow up would be a preferable endpoint. However, the 6-month endpoint in the current study was chosen as little additional change has been shown to occur beyond this point in common musculoskeletal conditions, such as low back pain [53]. We used an established diagnostic classification system and validated questionnaires; we also chose a main outcome measure that is not commonly used in prognostic studies, albeit that it might provide a more meaningful outcome in patients with musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 99%